Renegades - Meyer, Marissa (Meyer, Marissa. Renegades, 2017)
The Renegades are human, but with extraordinary abilities. They emerged from the ruins of a crumbled society and established peace and order where chaos reigned. As champions of justice, they remain a symbol of hope and courage to everyone... except the villains they once overthrew. Nova has a reason to hate the Renegades, and is on a mission for vengeance. Adrian is a Renegade boy who believes in justice-- and in Nova. But Nova's allegiance is to a villain who has the power to end them both.--